Pengaruh Religiusitas, Pemahaman Akuntansi Syariah, dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Akuntansi Syariah UIN Salatiga Berkarir Di Lembaga Keuangan Syariah - sholihah, almaratus; Wulandari, Cory (UIN Salatiga, 2023)
The purpose of this study was to determine how the influence of religiosity, understanding of sharia accounting and job market considerations on the interest of sharia accounting students at IAIN Salatiga in a career in Islamic financial institutions. This study uses a quantitative descriptive analysis method with a research instrument questionnaire distributed online with the help of Google form. A total of 70 students majoring in Islamic accounting, class 2018 IAIN Salatiga. The data technique in this study uses Multiple Linear Regression analysis. The results of the analysis show that religiosity does not have a significant effect on the interest of sharia accounting students for careers in Islamic financial institutions. while understanding of sharia accounting and labor market considerations have a significant influence on the interest of sharia accounting students in a career in Islamic financial institutions.Keywords: religiosity, understanding accounting sharia, job market considerations, islamic financial institutions